Derivation of road noise improvement factor within a suspension system using the inverse substructuring method. (December 2019) - Kang, Yeon June; Kim, Jun Gu; Song, David P; Ih, Kang Duck
This research aims to develop a method to efficiently reduce the body input force from the chassis due to road-induced excitation. To this end, the frequency response function–based substructuring method is employed to model the vehicle cross member and coupling points. Using this model, the dynamic stiffness modification factor of elastic bushing at the effective path is predicted for reducing road noise. Because of the difficulties in directly obtaining dynamic properties of body mount bushings pressured into the sub-frame, the frequency response function–based substructuring model and inverse formulation method are used to indirectly estimate the bushing's dynamic properties. Therefore, the primary focus of this study is to validate the feasibility of using the inverse formulation method for deriving road noise improvement factor on a simple cross member application. In this feasibility validation, road excitation is simply substituted with a shaker excitation in vertical direction. The previously developed suspension rig that enables a direct measurement of the body input force at the coupling points and the specially developed cross member jig are used for the validation test.